Avaliação clínica dos tempos de aplicação do peróxido de hidrogênio no clareamento em consultório - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2014)
The aim of this clinical study was to compare the bleaching efficacy and tooth sensitivity (TS) of in-office bleaching applied under different times protocol. Fifty-three patients with right superior canine darker than A3 were selected to participate in this single-blind randomized trial. The participants were distributed in three groups: the bleaching agent was applied once (1x15) for 15 minutes or refreshed every 15 minutes for two (2x15) or three (3x15) times at each bleaching appointment. The buccal surfaces of the anterior teeth were bleached, in two sessions, using a 35% (Whiteness HP Maxx, FGM) with one-week interval. The color change was evaluated by using the VITA Easyshade Spectrophotometer (Vita Zahnfabrik). Participants recorded TS with a five-point verbal scale. Color change was analyzed by two-way ANOVA and Tukey’s tests (α=0.05). The absolute risk of TS and TS intensity evaluated by Fisher’s exact test and two-way ANOVA and Tukey’s tests, respectively (α= 0.05). The reduction of number of bleaching application (1x15 or 2x15) decreased the bleaching efficacy (p < 0.05). 83%, and 94% of patients from the 2x15 and 3x15 groups, respectively, experienced tooth sensitivity (p < 0.05), however, only 3x15 group was statistically significant higher than 1x15 (p < 0.05). The intensity of sensitivity was lower for the 1x15 in comparison to other groups (p < 0.05). The reducing the number of times the in-office bleaching gel to be applied significant decrease the TS, but also the bleaching efficacy. Intermediary results in terms of bleaching efficacy and TS was found when 2 x 15-min of application was performed in each clinical appointment.
Keywords: Clareamento Dental; Ensaio Clínico Controlado Aleatório; Sensibilidade da Dentina; Tooth Bleaching; Randomized Controlled Clinical Trial; Tooth Sensitivity; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA